Economic Benefits of Empowering Women in Agriculture: Assumptions and Evidence. Issue 2 (1st February 2021) - Anderson, C. Leigh; Reynolds, Travis W.; Biscaye, Pierre; Patwardhan, Vedavati; Schmidt, Carly
Abstract: Systematic reviews and meta-analyses generally focus on intervention impacts or outcomes. Less common, however, are reviews of the assumptions and theory underlying the pathways between intervention and outcome. We consider the hypothetical case for interventions to empower female farmers, either by prioritising women for new investments or re-allocating existing resources. Empowerment is defined as increased women's decision-making authority related to agricultural resources, management and production, and income. We hypothesise two avenues through which productivity or health benefits might arise: (i) eliminating female-male differences in, e.g. input access; or (ii) leveraging gendered risk, time, and social preferences leading women to differentially allocate resources. A review of evidence highlights the extent of support for the baseline, behaviour change, and economic benefit assumptions behind these hypothesised avenues. Findings suggest returns to investing in female farmers could be significant in various contexts but estimates of economic returns to empowering women in agriculture remain limited.